An Overview of Ethical and Legal Considerations of Assisted Reproductive Techniques - Nagy, Zsófia (Central European Academy Law Review, 2023)
With the constant evolution of technology in the field of medicine, new ethical questions must be answered. In particular, medically assisted reproduction triggers bioethical disputes nowadays, despite the idea that reproduction without sexual intercourse is not newfangled. When discussing techniques such as artificial insemination, gamete donation, post-mortem fertilisation, in vitro fertilisation, and surrogacy, the traditional concepts of parenthood, genetic filiation, reproductive autonomy, and human dignity are placed under exposition. The sensitive nature of these bioethical issues is present in the diversity of the legislation in Europe and is markedly enstamped in the hesitant attitude of the European Union and the Council of Europe.